Inhibitory effect of Thymus vulgaris and Origanum vulgare essential oils on virulence factors of phytopathogenic Pseudomonas syringae strains - Carezzano, Maria Evangelina (2017)
Pseudomonas syringae is a phytopathogenic bacterium that causes lesions in leaves during the colonisation process. The damage is associated with production of many virulence factors, such as biofilm and phytotoxins. The essential oils of Thymus vulgaris (thyme) and Origanum vulgare (oregano) have been demonstrated to inhibit P. syringae. The aim of this study was to investigate the effects of T. vulgaris and O. vulgare essential oils on production of virulence factors of phytopathogenic P. syringae strains, including anti-biofilm and anti-toxins activities. The broth microdilution method was used for determination of MIC and biofilm inhibition assays. Coronatine, syringomycin and tabtoxin were pheno- and genotypically evaluated. Both oils showed good inhibitory activity against P. syringae, with MIC values from 1.43 to 11.5 mg·ml−1 for thyme and 5.8 to 11.6 mg·ml−1 for oregano. Biofilm formation, production of coronatine, syringomycin and tabtoxin were inhibited by thyme and oregano essential oil in most strains. The results presented here are promising, demonstrating the bactericidal activity and reduction of virulence factor production after treatment with thyme and oregano oil, providing insight into how they exert their antibacterial activity. These natural products could be considered in the future for the control of diseases caused by P. syringae.